The role of autonomous learning in the study of grammar by economics and foreign language students (pedagogical profile with two areas of training) - Nina S. Shvaikina; Alexander A. Popel; Viktoria M. Volova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Currently, an integral part of the learning process is the development and honing of the skills of competent use of a foreign language – the most important criterion in any field. The sphere of economics and pedagogy is no exception, because specialists in the presented direction should formulate thoughts succinctly, both in written and oral forms. In pedagogical science, there is a search for effective means to improve grammatical skills and abilities. In this paper, the authors present autonomous learning as an effective tool in the study of grammar, which implies that students should have the opportunity to learn the rules themselves and consolidate them in practice. Autonomous learning implies the improvement of self-regulation and critical thinking, which, in turn, is extremely important in possible non-standard situations that may arise in the course of professional activity. The limitless possibilities of autonomous learning are various online resources, interactive tasks, audio and video materials, electronic literature, grammar exercises. It is thanks to such aspects that students enrich their vocabulary, as well as significantly improve their pronunciation and text construction skills. The aim of the work is to reveal the specifics of the format of autonomous learning by students of the direction "Economics and foreign language" in the study of grammar. The object of the study is the field of formation of autonomous learning skills in the study of grammar. The subject of the study is the introduction of M. Schmitt’s autonomous model "Integrated Learning" in the process of studying grammar of students in the specialties "Economics and foreign language". The scientific novelty of this research is expressed in the creation of its own autonomous learning model and its components. The practical significance of the work is in the possible application of the proposed exercises in autonomous learning by students of the specialization under study. The results of this study will contribute to the field of linguodidactics, as well as attract the attention of teachers, students and all interested parties to innovative approaches in teaching grammar. In addition, the findings allow us to identify effective strategies for autonomous learning that can be used in teaching practice in any field.